Synthesis and Characterization of Silver Nano Particles for EDM Applications. (2017) - Banne, Shivaji V.; Patil, M.S.; Kulkarni, R.M.; Patil, S.J.
Abstract: Over the past few decades, nano particles research of noble metals such as silver exhibited as an intense area of scientific interest due to their significantly distinct applications in biomedical, optical and electronic fields from their bulk counterparts because of their smaller particle size, higher surface area and various other effects. These silver nano particles can be synthesized by various methods: Reduction either by using Citrate or Sodium Borohydride, Ion Implantation and Biogenic Synthesis. Amongst these, Sodium Borohydride is used in excess for reduction of silver nitrate and stabilize the silver nano particles. Sodium Borohydride being a strong reducing agent may lead to secondary reaction. An ice bath facilitates to slow down the reaction rate and eliminates secondary reactions. If agglomeration of nano particles occurs, PVP is added during reaction. To characterize the nano particles Ultraviolet Visual Spectroscopy, Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD) can be employed. Borohydride reduction method produces 30-100 nm particles.